2022
DOI: 10.1002/adma.202208182
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Surface Acidity of Mixed Conducting Electrodes: Recovery of Si‐Induced Degradation of Oxygen Exchange Rate and Area Specific Resistance

Abstract: metal oxide-based gas sensors, for which device performance relies on rapid oxygen exchange reactions at the gas-solid interfaces. [1][2][3][4][5][6][7] In SOFCs, the oxygen reduction reaction (ORR) occurs at the cathode and the corresponding polarization resistance depends on the adsorption/dissociation of oxygen species on the surface, followed by charge transfer between the surface and the adsorbed species, and finally the incorporation of charged oxygen ionic species into the electrode lattice. Although ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 61 publications
5
10
0
Order By: Relevance
“…Through a systematic study of different additives, it was found that oxides described by Smith as basic, for example, lithia or calcia, resulted in an increased response rate, while those considered acidic, for example, silica or alumina, suppressed the response speed 18 . In line with the findings of Nicollet et al., the relaxation kinetics of PCO onto which Si‐species had been added to the surface responded considerably slower to stepwise oxygen changes than the pristine material, Figure 4B (blue) 3,18,27,43,44 . On the other hand, the basic additive lithia, resulted in an increased response rate, see Figure 4B (yellow).…”
Section: Case Studiessupporting
confidence: 75%
See 4 more Smart Citations
“…Through a systematic study of different additives, it was found that oxides described by Smith as basic, for example, lithia or calcia, resulted in an increased response rate, while those considered acidic, for example, silica or alumina, suppressed the response speed 18 . In line with the findings of Nicollet et al., the relaxation kinetics of PCO onto which Si‐species had been added to the surface responded considerably slower to stepwise oxygen changes than the pristine material, Figure 4B (blue) 3,18,27,43,44 . On the other hand, the basic additive lithia, resulted in an increased response rate, see Figure 4B (yellow).…”
Section: Case Studiessupporting
confidence: 75%
“…Additionally, the basic additive can react with the Si-species, forming a silicate (shown in green in Figure 5D) which is expected to exhibit intermediate levels of acidity. 44 As expected, significant degradation was also found following infiltration with acidic Cr-additives. Here, also subsequent recovery was achieved by follow-up infiltration with basic additive (Lior Ca-species).…”
Section: Oxide Additives-solid Oxide Fuel Cell Cathodessupporting
confidence: 68%
See 3 more Smart Citations